2020
DOI: 10.3389/fbioe.2020.00656
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Average Shape and Principal Variations of the Human Talus Bone Using Statistic Shape Model

Abstract: Due to the complexity of articular interconnections and tenuous blood supply to the talus, talus fractures are often associated with complications (e.g., avascular necrosis). Currently, surgically fusing the talus to adjacent bones is widely used as treatment to talus fractures, but this procedure can greatly reduce mobility in the ankle and hindfoot. Alternatively, customized talus implants have shown an overall satisfactory patient feedback but with the limitation of high expenses and time-consuming manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Figure13demonstrates the magnitude fields of shape deviations between our mean shape and the best talar shape found byTrovato et al (2017), and the mean shapes obtained byLiu et al (2020) andLenz et al (2021). The deviation fields indicated that the best talar shape presented by Trovato et al was more deviated from our predicted mean shape than the mean shapes predicted byLiu et al and …”
supporting
confidence: 49%
See 3 more Smart Citations
“…Figure13demonstrates the magnitude fields of shape deviations between our mean shape and the best talar shape found byTrovato et al (2017), and the mean shapes obtained byLiu et al (2020) andLenz et al (2021). The deviation fields indicated that the best talar shape presented by Trovato et al was more deviated from our predicted mean shape than the mean shapes predicted byLiu et al and …”
supporting
confidence: 49%
“…Shape deviations of the best talar shape presented by Trovato et al (2017), and the mean shapes obtained by Liu et al (2020) and Lenz et al (2021) from the mean shape predicted in this study [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The contribution of third, fourth, and fifth PC modes can be considered as a local variation among most areas of articulations (Talar neck angle 2, talar neck angle 3, talar neck depth 2, talar neck depth 3 in geometric measurements). Similar observations are found by Liu et al 22 on adult talus with less variation in each mode as their samples are all healthy and intact.…”
Section: Principal Component Analysis Of Three-dimensional Models Of Talussupporting
confidence: 88%